2019
DOI: 10.1016/j.tcr.2019.100172
|View full text |Cite
|
Sign up to set email alerts
|

Displaced osteochondral fracture of the posterolateral tibial plateau associated with an acute anterior cruciate ligament injury

Abstract: An osteochondral fracture of the posterolateral tibial plateau associated with an anterior cruciate ligament (ACL) injury in a 24-year-old boy is reported. Anterior cruciate ligament rupture is accompanied by bone contusions resulting from the impact of the posterolateral tibial plateau on the anterior part of the lateral femoral condyle. The osteochondral fracture of the posterolateral tibial plateau matched the site where the bone bruise is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…These injuries, also known as "apple-bite" fractures, represent the most frequent indirect sign of ACL tear. 3,5,22,29 Also, lateral meniscus tears and impaction of the lateral femoral condyle are frequently associated with these injuries. 3,5,22,30 Chang et al found both a greater risk of lateral meniscus injury with more than 6.3 mm of lateral joint depression and of ACL tear when the volumetric lateral joint depression is less than 209.6 mm 2 , and/or there is more than 5.7-mm lateral joint widening.…”
Section: Surgical Techniques For Reconstructionmentioning
confidence: 99%
“…These injuries, also known as "apple-bite" fractures, represent the most frequent indirect sign of ACL tear. 3,5,22,29 Also, lateral meniscus tears and impaction of the lateral femoral condyle are frequently associated with these injuries. 3,5,22,30 Chang et al found both a greater risk of lateral meniscus injury with more than 6.3 mm of lateral joint depression and of ACL tear when the volumetric lateral joint depression is less than 209.6 mm 2 , and/or there is more than 5.7-mm lateral joint widening.…”
Section: Surgical Techniques For Reconstructionmentioning
confidence: 99%
“…The tibiofibular arch plays an important role in bearing downward forces of the lateral compartment of the knee joint. 5 , 16 Therefore, we speculate that bone bruises of the fibular head occurred because of a large degree of traumatic energy that could not be limited to the lateral tibial plateau. Our hypothesis was supported by our finding that no patient had a grade I bone bruise classified as type d, which shows that the energy was too small to reach the fibular head in patients with grade I bone bruises.…”
Section: Discussionmentioning
confidence: 96%
“…Giordano et al [ 8 ] described these posterolateral corner sheared fractures of the tibial plateau as “apple-bite” fractures, which were rare and infrequently mentioned in previously published reports. Also, these fractures were typically associated with ACL rupture, lateral meniscus injury, and MCL tears, due to rotational trauma when the knee was in a slight valgus position and flexed [ 8 10 ]. In some cases with possible ACL rupture, it is challenging to diagnose posterolateral corner rim fractures with radiographs due to the superimposition of the larger medial condyle [ 11 ].…”
Section: Case Presentationmentioning
confidence: 99%